2018
DOI: 10.1186/s12915-018-0519-2
|View full text |Cite
|
Sign up to set email alerts
|

Caring for parents: an evolutionary rationale

Abstract: BackgroundThe evolutionary roots of human moral behavior are a key precondition to understanding human nature. Investigations usually start with a social dilemma and end up with a norm that can provide some insight into the origin of morality. We take the opposite direction by investigating whether the cultural norm that promotes helping parents and which is respected in different variants across cultures and is codified in several religions can spread through Darwinian competition.ResultsWe show with a novel … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…It was shown that honest begging results in decreased variance of collected food among siblings, which leads to a higher mean number of surviving offspring. Furthermore, in Garay et al [28] the evolutionary roots of human morality were studied. It was found that the biological version of the Fifth commandment, called the Fifth rule (“ During your reproductive period, give away from your resources to your post-fertile parents ”) can spread by means of natural selection, by increasing the survival rates of the family members.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that honest begging results in decreased variance of collected food among siblings, which leads to a higher mean number of surviving offspring. Furthermore, in Garay et al [28] the evolutionary roots of human morality were studied. It was found that the biological version of the Fifth commandment, called the Fifth rule (“ During your reproductive period, give away from your resources to your post-fertile parents ”) can spread by means of natural selection, by increasing the survival rates of the family members.…”
Section: Introductionmentioning
confidence: 99%
“…We use the term “offspring gratitude” to emphasize the difference from other kinds of gratitude as e.g. “upstream reciprocity” [52, 53], and the Fifth rule [28]. Now we can make precise what we understand under “ self-sacrificing life history strategy ”: an individual having this phenotype is altruistic and grateful in juvenile age, and is a provider parent during adult age.…”
Section: Introductionmentioning
confidence: 99%
“…Older women are likely to be post-menopausal and therefore unable to directly reproduce, making the possible indirect fitness gains minimal; and fathers of adults may physiologically be able to reproduce in old age, but their fertility will be constrained by mate availability, as it is likely these older men will be partnered with women of a similar age who are post-menopausal making reproduction unlikely 21 . Despite the apparent limited inclusive fitness gains to be had from the behaviour, caring for elderly parents is a cross-cultural norm.At present, we are only aware of one model attempting to address elder care from a fitness maximising framework 22 . Here, in a demographic model it is proposed that upwards intergenerational care would be selected for due to the possible reciprocal benefits of the behaviour.…”
mentioning
confidence: 99%
“…At present, we are only aware of one model attempting to address elder care from a fitness maximising framework 22 . Here, in a demographic model it is proposed that upwards intergenerational care would be selected for due to the possible reciprocal benefits of the behaviour.…”
mentioning
confidence: 99%
See 1 more Smart Citation